Status of Citrus Canker in Ethiopia and Malaysia, and Characterization of the Causal Agent - Kidanu, Eshetu Derso (2006)
Citrus canker disease surveys were conducted between August to November 2003 in Ethiopia and between January to April 2004 in West Malaysia. The pathogens were isolated and identified based on morphological characteristics and pathogenicity tests on seedlings of citrus cultivars using isolates collected from West Malaysia. Biochemical characterizations of the isolates were also carried out using standard determinative tests. In Ethiopia, citrus canker was observed only on sour orange (Citrus aurantium) and Mexican lime (C. aurantifolia). Disease incidence in the field on Mexican lime leaves in Ethiopia was 71.4% and severity was 26.8%; incidence on fruits was 30% and severity 21.25%. This is the first confirmed report of the disease in Ethiopia. In Malaysia, the disease was observed on Mexican lime (C. aurantifolia), pomelo (C. grandis) and kaffier lime (C. hysterix). Overall, the disease incidence in Malaysia was of 36.5% and severity of 12.5% on leaves, while incidence on fruits was 18.7% and severity 7.5%. Growth of X. axonopodis pv. citri in yeast dextrose chalk agar (YDCA) was not as fast as in peptone sucrose agar (PSA) or nutrient glucose agar (NGA). However, the former medium was very selective to Xanthomonas species. There were highly significant differences in lesion size for cultivars (P < 0.01) but not for isolates. Significant positive regression (P < 0.05) was observed between lesion size and time after inoculation. Repeated measure analysis using general linear model (GLM) for correlation between times after inoculation was highly significant (P < 0.01). No variation in pathogenicity was observed among the isolates. Population sizes increased by over 2 Log cfu/lesion on Mexican lime and nearly by 1.5 Log units on sour orange and pomelo and remained around the initial inoculum level on calamondin. Significant positive correlations were observed between X. axonopodis pv. citri population and lesion size on sour orange (r =0.57, P =0.024), pomelo (r =0.73, P =0.018) and Mexican lime (r = 0.76, P = 0.001). The correlation was relatively the highest for Mexican lime (r = 0.76) and lowest for calamondin (r=0.25). The interactions between isolates and cultivars were highly significant (P < 0.01). Tukey tests showed no significant differences in reaction to X. axonopodis pv. citri isolates between sour orange and pomelo, sour orange and sweet orange, Mexican lime and grapefruit, and also between calamondin and sweet orange. The six citrus test cultivars were all susceptible to the 15 X. axonopodis pv. citri isolates and citrus canker lesions were induced on the detached leaves. There was highly significant (P < 0.01) interaction between cultivars and all strains. Disease severity on detached leaves was significantly correlated (P < 0.01) with disease severity ratings in attached leaf test studies and was relatively the highest (r=0.97) for Mexican lime. In the biochemical characterization study, all 15 isolates of X. axonopodis pv. citri showed similar results using standard determinative tests. Field host ranges for citrus canker in Ethiopia were Mexican lime and sour orange, while in West Malaysia it appears to be wider than in Ethiopia. In conclusion, on the basis of their host range in seedling tests, morphological characteristics, pathogenicity tests, population growth in planta and biochemical characteristics, the 15 representative West Malaysian isolates of X. axonopodis pv. citri were characterized to be associated to the Asiatic type (“A” type) citrus canker. Sour orange, pomelo, Mexican lime, calamondin grapefruit and sweet orange were all susceptible to the 15 X. axonopodis pv. citri isolates.